2008
DOI: 10.1016/j.febslet.2008.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Redox state and gender differences in vascular smooth muscle cells

Abstract: Vascular smooth muscle cells (VSMC) have been isolated from male and female rat aorta and studied to assess their susceptibility to ultraviolet radiation-induced oxidative stress. Interestingly, a gender difference, in terms of reactive oxygen species production, was detected in both basal and irradiated VSMC. Namely, VSMC from male rats were more susceptible to radiation-induced stress and easier underwent apoptosis in comparison to cells from female rats. Conversely, the latter, in the same experimental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 29 publications
6
72
0
Order By: Relevance
“…Gender-related differences in the oxidative stress response and T-cell immunity Gender disparity in redox imbalance and susceptibility to apoptotic signals results in the increased risk of cardiovascular pathogenesis (174), asthma (171), melanoma (127), and lung cancer (287). Whether or not the gender-dependent regulation of oxidative stress and apoptosis is associated with T-cell immune response in these diseases is unknown and warrants further investigation.…”
Section: G Agingmentioning
confidence: 99%
“…Gender-related differences in the oxidative stress response and T-cell immunity Gender disparity in redox imbalance and susceptibility to apoptotic signals results in the increased risk of cardiovascular pathogenesis (174), asthma (171), melanoma (127), and lung cancer (287). Whether or not the gender-dependent regulation of oxidative stress and apoptosis is associated with T-cell immune response in these diseases is unknown and warrants further investigation.…”
Section: G Agingmentioning
confidence: 99%
“…Male SMCs were shown to produce more superoxide anion and SOD levels were lower in SMCs from male than female mice [50]. UVB-induced radiation resulted in apoptosis of SMCs that was also greater in male compared to female mice [50]. Interestingly, nitric oxide regulates SOD levels, but results using a carotid injury model demonstrated that males increase SOD levels in response to nitric oxide whereas females do not [51].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 87%
“…Deletion of SOD abolished sex diferences in myogenic tone of mesenteric arteries from male compared to female mice [49]. Additional studies demonstrated that SMCs harvested from male and female rat aortas respond diferently to ultraviolet B (UVB)-induced radiation [50]. Male SMCs were shown to produce more superoxide anion and SOD levels were lower in SMCs from male than female mice [50].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they showed that male cells had more cytoskeleton damage due to UV radiation, which might lead to their increased apoptosis. 64 In their recent study, they further analyzed female cells' apoptotic resistance by studying their behavior in anoikis, a type of cell apoptosis, via detachment from substrate. Their results confirmed that number of detached cells in female were lower both prior to UV radiation and after radiation.…”
Section: Atherosclerosismentioning
confidence: 99%